Evaluasi Program Penataan Kawasan Pesisir Kota Ternate (Studi Kasus Program Reklamasi Pantai Halmahera 2014) - Hi Garuan, Ismar; Suranto, Suranto (Universitas Muhammadiyah Yogyakarta, 2016)
Reclamation is an activity held for the sake of increasing the benefits of land resources in terms of environment andsocial economic by the methods of reclamation and drainage. Coastal reclamation in Indonesia has been done sincethe year of 1979 and is continuously implemented until present time. The purpose of this research is to evaluate thecoastal reclamation program and to recognize the impact of reclamation program at Halmahera beach in Ternate. Theresearch methodology used is qualitative research, whilst the research itself is conducted in Halmahera beach in Soa-Sio village, Ternate city. Data gathering techniques used in this research are observation, interview, and documentation.The analysis of this research is done by describing the coastal reclamation program using qualitative descriptiveanalysis. The results of this research are, 1) in terms of context; regulations, the impact of reclamation needs to bereviewed, the coastal reclamation planning has been appropriate but the purpose of reclamation program is yet to beachieved and longer process is necessary in achieving the intended purpose. 2) In terms of input; human resources,facilities and infrastructure, and funding have been in accordance with the provisions. However improvement is necessaryfor a better result in the future. 3) In terms of Halmahera coastal reclamation process; an issue concerning landlicense by Legal Aid Institution (LBH) of Ternate occurs, and the application period on the year of 2013 was notutilized. Therefore, evaluation toward future reclamation program is necessary. 4) In terms of product; based on thefield observation, spatial planning in Ternate has been managed in a good manner. 5) The impacts of Halmaheracoastal reclamation program; impaired quality of seawater occurs due to ground work activities and public facilitiesconstruction during the construction process based on the indicator of Ministerial Decree LH No. 51 year 2004 aboutwater quality standard. The arousal of coastal aquatic biota disruption and coastal aquatic bio-diversity reduction,indicated by the abundance of planktons and benthos. Social jealousy due to the use of outside workers instead oflocal workers during the construction. The aesthetic improvement of the environment (safe, comfortable, beautiful)emerges for the implementation of ground care. The increase of local economic activities, signified by the economicactivities of the local area and the increase of merchantsâ income. The increase of job opportunities due to theopening job field for land manager and mini market employees. From several impacts above, preventive measures andutilization of the reclamation program need to be done by government in order to increase job opportunity andsocietyâs welfare.